2018
DOI: 10.1016/j.nedt.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

In defence of the viva voce: Eighteen candidates' voices

Abstract: The viva voce examination, as experienced by candidates, is not always a fair one. We recommend engagement of the academic community to promote best practice in the "living voice" examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Students' perception of their doctoral defense is related to the behavior of the committee members during the defense. The choice of committee members, and their impact on all levels of the defense is highlighted in [18]. This study looked at candidates' perception of the defense through semi-structured interviews (n = 18).…”
Section: Students' Perception Of the Defensementioning
confidence: 99%
See 2 more Smart Citations
“…Students' perception of their doctoral defense is related to the behavior of the committee members during the defense. The choice of committee members, and their impact on all levels of the defense is highlighted in [18]. This study looked at candidates' perception of the defense through semi-structured interviews (n = 18).…”
Section: Students' Perception Of the Defensementioning
confidence: 99%
“…The questions on student perception were constructed based on a number of sources. First of all, questions regarding emotions were included because the emotional level of the defense was identified in the literature as an important element [16,18]. The studied emotions include nervousness before, during, and after the defense.…”
Section: Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing work on doctoral assessment is mostly limited to studying the viva voce in the United Kingdom [1][2][3][4][5][6][7][8], the assessment of the thesis in Australia [9], and the experience in New Zealand for non-native English speaking candidate [10]. Some work has also looked at the different formats used for the doctoral defense in European countries, in the light of potential pan-European standardization of the defense procedures [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work indicated that the defense has three dimensions: the scholarly dimension, the emotional (affective) dimension, and the cultural dimension [5,10]. Most research on the doctoral defense in the past has focused on the scholarly dimension, and how the quality of doctoral research is assessed during the defense, as well as the relation between the evaluation of the written thesis and the evaluation of the oral defense [2,3,8,12,[21][22][23]. So far, work on the affective dimension is limited to evaluating students' perception of the defense [2,5,20,[24][25][26], with each of these studies focusing only on one defense format.…”
Section: Introductionmentioning
confidence: 99%